Bacterial cellulose as a next-generation membrane material for selective transport: properties, fabrication, and applications - Calhan, Aslihan; Hasanoglu, Ayca (SPRINGER, 2026)
Bacterial cellulose (BC) is an emerging, sustainable biomaterial that distinguishes itself from plant-derived cellulose by being free from lignin and hemicellulose and its ability to be synthesized from various organic waste sources. The eco-friendly production and high design flexibility make BC a promising material for advanced membrane technologies. Through careful control of its production conditions and physical or chemical modifications, BC's structural and functional properties can be tailored for diverse applications. Current limitations of bacterial cellulose applications include its high production costs, limited mechanical strength for some particular applications and susceptibility to microbial contamination. This review provides a comprehensive overview of BC as a next-generation membrane material for selective transport, covering its synthesis, modification strategies, and application-specific design. Emphasis is placed on BC's role in fields where controlled mass transfer is critical, such as drug delivery, food packaging, wastewater treatment, and filtration systems. For each domain, the mechanisms of transport across the BC membrane are discussed, focusing on the types of phases involved (gas, liquid, or solid) and the nature of the components being selectively transferred. The review classifies BC membranes according to application sectors and highlights their performance in facilitating selective transport through mechanisms such as adsorption, permeability, and diffusion. By examining recent research trends and innovations, this study emphasizes the versatility and adaptability of bacterial cellulose in both conventional and emerging membrane technologies, contributing to its broader integration into sustainable and functional material systems.
Keywords: Bacterial cellulose; Membrane material; Mass transfer; Selective transport; Water treatment; Biomedical applications; IN-SITU SYNTHESIS; MEDICAL APPLICATIONS; CARBON; WATER; NANOCOMPOSITE; NANOPARTICLES; ALGINATE; REMOVAL; COPPER; Materials Science; Polymer Science